Synthesis and reference standard establishment of N-(2-hydroxyphenyl)acetamide - Tran, Thị Bích Ngân; Trinh, Hoàng Dương; Huynh, Thị Ngọc Dung; Thieu, Thị Thu Liễu; Le, Văn Út; Ha, Diệu Ly (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
N-(2-hydroxyphenyl)acetamide (impurity C according to USP) is a related impurity of acetaminophen arising from the synthesis process. Today, there has been no domestic research published on the synthesis process of impurity C, and it has to be ordered from abroad at a high cost. Based on the actual need for drug testing, this project was carried out with the aim of preparing and establishing the reference standard N-(2-hydroxyphenyl)acetamide. N-(2-hydroxyphenyl)acetamide is synthesized by the acetylation reaction of 2-aminophenol with acetic anhydride. The product, after synthesis, is purified and its structure is determined using modern analytical techniques such as UV-Vis, IR, NMR; and its purity is determined by HPLC.